Oil platforms and private security in spanish law: An approach - Areal Ludeña, Santiago (2016)
Within the scope of the Spanish legislation, in this article we will develop the regulation about private security on oil rigs. In this sense, it is necessary to give a possible legal responses to this fact, because of the current drawbacks for proper regulation in the European country. It is therefore necessary to provide answers from the different perspectives of law such as the Public, Private International Law, Administrative Law, Commercial Law and Labor Law, International Law which will lead us to determine what should be the role of State.